Новые хищнецы юга СССР (Heteroptera, Reduviidae) - Пучков, П.В. (Вестник зоологии, 1984)
New Reduviid Bugs from the Southern USSR (Heteroptera, Reduviidae). Putshkov P. V. — Vestn. zool., 1984, No. 1. Two outstanding reduviid bug species are described as new. Oncocephalus paternus sp. n.—a brachypterous species from the Crimea (Morskoye, Sudak); Plocaria turkestanica sp. n.— second full winged representative of the genus in Palearctics found in Kazakhstan (south-eastern margin of the Kyzyl-Kum desert). Wahrmania Dispons, 1964 (type species by original designation and monotypy: Wahrmania katznelsoni Dispons, 1964) is sunk in synonymy of Ploiaria Scopoli, 1786.